2021
DOI: 10.3389/fcvm.2021.704657
|View full text |Cite
|
Sign up to set email alerts
|

The β2-Subunit of Voltage-Gated Calcium Channels Regulates Cardiomyocyte Hypertrophy

Abstract: L-type voltage-gated calcium channels (LTCCs) regulate crucial physiological processes in the heart. They are composed of the Cavα1 pore-forming subunit and the accessory subunits Cavβ, Cavα2δ, and Cavγ. Cavβ is a cytosolic protein that regulates channel trafficking and activity, but it also exerts other LTCC-independent functions. Cardiac hypertrophy, a relevant risk factor for the development of congestive heart failure, depends on the activation of calcium-dependent pro-hypertrophic signaling cascades. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In this study, we first corroborated the expression pattern of the five Ca v β 2 splice variants (Ca v β 2a -Ca v β 2e ) in cultured ARCs. RT-PCR analyses confirmed that Ca v β 2b is the predominant splice variant and that the other ones are detected at very low levels (Figure 1B) as also ocurrs in neonatal rat cardiomyocytes (Pickel et al, 2021). In order to detect the expression of protein Ca v β 2b in cardiomyocytes, we produced an antibody that specifically recognizes and targets the N-terminus of this Ca v β 2 splice variant.…”
Section: Ca V β 2b -Apex2 Expression In Adult Rat Cardiomyocytesmentioning
confidence: 82%
“…In this study, we first corroborated the expression pattern of the five Ca v β 2 splice variants (Ca v β 2a -Ca v β 2e ) in cultured ARCs. RT-PCR analyses confirmed that Ca v β 2b is the predominant splice variant and that the other ones are detected at very low levels (Figure 1B) as also ocurrs in neonatal rat cardiomyocytes (Pickel et al, 2021). In order to detect the expression of protein Ca v β 2b in cardiomyocytes, we produced an antibody that specifically recognizes and targets the N-terminus of this Ca v β 2 splice variant.…”
Section: Ca V β 2b -Apex2 Expression In Adult Rat Cardiomyocytesmentioning
confidence: 82%
“…An instance supporting this hypothesis is CaVβ4C, which interaction with HP1γ has been shown as mandatory to localize to the nucleus in mammalian cells ( Hibino et al, 2003 ), while the truncation of a large part of its GK domain cut off the exclusive requirement of SH3/GK interaction for nuclear docking of CaVβs proteins. The molecular aspects of nuclear targeting were less studied for CaVβ2 and CaVβ3, for which some studies mentioning their binding with chaperone proteins may be relevant in supporting their tackling to the nuclei ( Zhang et al, 2010 ; Pickel et al, 2021 ).…”
Section: Cavβ As a Self-sufficient Nuclear Proteinmentioning
confidence: 99%
“…The authors hypothesized that the potential mechanism modifying disease phenotype was based on the attenuation of CaV-dependent Ca 2+ current associated with CACNB2 mutations. However, an additional possibility came out a few years later with a study that correlated the reduced cardiomyocyte hypertrophy to a CaV-independent CaVβ2 function ( Pickel et al, 2021 ). CaVβ2 localization and activity in cardiomyocyte nuclei were shown to significantly regulate Calpain activity and Calpastatin expression ( Pickel et al, 2021 ), a pro-hypertrophic protease and its inhibitor, respectively.…”
Section: Implication Of Cavβs In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxiliary subunits β belongs to the MAGUK-scaffolding protein family, a cytosolic soluble protein with high affinity binding to channel, including four subtypes of β 1 - β 4 [ 16 ]. The mutation of β subunit is associated with arrhythmia and stroke [ 16 ].…”
Section: Introductionmentioning
confidence: 99%